Behavioural and Social Drivers of Seasonal Influenza Vaccination (BeSD IN) in Jordan - Ayman Bani Mousa; Nizar Maswadi; Zaid Al-Hamdan; Mohammad Alhawarat; Lora Al Sawalha; Raid Anwar Al-Shboul; Feras Ibrahim Hawari (Vaccine: X)
Background: Cultural norms and social beliefs play a significant role in shaping attitudes toward vaccination. The Jordanian Ministry of Health, with the support of international health organizations, has launched several initiatives to improve influenza vaccination coverage. However, challenges persist, particularly among certain demographic groups, making it essential to understand the underlying knowledge, behaviors, and attitudes influencing vaccination decisions. This study aims to explore these factors through a large-scale survey conducted among healthcare workers, pregnant women, and elderly people in Jordan. Method: A cross-sectional survey was designed to identify social and behavioral drivers (BeSD) of influenza vaccination among three key target groups in Jordan: healthcare workers, pregnant women, and the elderly. A convenience sample comprising 1,500 participants was recruited from the three target groups. The sample randomly selected from the three regions in Jordan, Data were collected through interviews conducted by trained and qualified research assistants. Result: The study revealed that 82.9 % of participants were aware of the influenza vaccine, with healthcare workers showing the highest awareness at 95 %, followed by pregnant women at 76 %, and the elderly at 70 %. Despite high awareness, only 45.6 % of respondents had been vaccinated in the past two years. Healthcare workers had the highest vaccination rates (65 %), while pregnant women (30 %) and the elderly (25 %) exhibited lower rates, primarily due to concerns about vaccine safety and accessibility challenges. Misconceptions were common, with 30 % of participants believing the flu vaccine causes influenza, and 25 % doubting its efficacy. These misconceptions were more prevalent among the elderly and rural populations. Access and affordability were significant barriers, particularly for the elderly, with many reporting difficulties in traveling to vaccination centres and lacking insurance coverage. Conclusion: To improve influenza vaccination rates, targeted public health campaigns should be conducted to correct misconceptions, especially among the elderly and pregnant women. Possible plans of action for improving uptake rates are improving accessibility by organizing mobile clinics, offering subsidized vaccines, and giving healthcare providers the necessary training to combat hesitancy among the general population. Further research needs to be undertaken to develop strategies for reassuring the public that vaccinations are safe and effective.